(untitled) (International Journal of Occupational Safety and Health, 2024)
Introduction: Work-related musculoskeletal disorders (WMSDs) are a serious problem that can affect the health and productivity of laundry workers. Workers who experience such disorders may experience pain, muscle stiffness, joint inflammation, and even serious injury. This study aimed to investigate the prevalence of work-related musculoskeletal disorders among laundry workers in North Sulawesi. Methods: This study is a quantitative descriptive cross-sectional survey conducted in March 2023 – April 2023 in Minahasa District North Sulawesi Province, specifically Tondano-Tomohon City. A total sample of 225 laundry workers was taken using the convenient sampling technique. The questionnaire used to assess WMSDs was the Nordic Body Map. The chi-square test was applied to find the association between age and musculoskeletal disorders among laundry workers. Results: Complaints felt in all parts of the worker’s body 5.38% were very painful, 17.81% were painful, 36.39% were rather painful, and 39.67% were not painful. The body part that experienced the most complaints of severe pain was back at 10.2%, feeling pain was the waist at 37.3%, feeling pain was the right arm at 47.1%, and no pain was the left elbow at 71.6%. Conclusion: The prevalence of work-related musculoskeletal disorders among the study population was significantly associated with age, sex, nutritional status, and work experience with musculoskeletal complaints (p<0.05). While there is no relationship between work duration and education level with musculoskeletal complaints (p>0.05). Therefore, appropriate interventions need to be made to improve working conditions, protect workers’ health, and minimize the risk of work-related musculoskeletal disorders in the laundry industry.